2012
DOI: 10.1038/nature11218
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of stem cell and progeny behaviour in physiological hair-follicle regeneration

Abstract: Tissue development and regeneration depend on cell–cell interactions and signals that target stem cells and their immediate progeny1. However, the cellular behaviours that lead to a properly regenerated tissue are not well understood. Using a new, non-invasive, two-photon (intravital instead of two-photon?) imaging approach we study physiological hair-follicle regeneration in real time in live mice. By these means we have monitored the behaviour of epithelial stem cells and their progeny2–4 during physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
349
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(359 citation statements)
references
References 22 publications
10
349
0
Order By: Relevance
“…Fourth, a large number of tissue stains, antibodies, and genetically directed cell marking methods have been developed for selectively visualizing a wide variety of skin structures. For completeness, we also note two additional experimental strengths arising from the surface location of skin that were not used in the present study: skin can be directly imaged in living animals and skin is highly amenable to experimental manipulation such as infection by transducing viruses to alter gene expression (31,32). Taken together, these attributes make mammalian skin a uniquely attractive tissue in which to study the interaction of macroscopic and microscopic patterning systems.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, a large number of tissue stains, antibodies, and genetically directed cell marking methods have been developed for selectively visualizing a wide variety of skin structures. For completeness, we also note two additional experimental strengths arising from the surface location of skin that were not used in the present study: skin can be directly imaged in living animals and skin is highly amenable to experimental manipulation such as infection by transducing viruses to alter gene expression (31,32). Taken together, these attributes make mammalian skin a uniquely attractive tissue in which to study the interaction of macroscopic and microscopic patterning systems.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, pioneering studies using in vivo live-imaging platforms have begun to provide access to continuous-time lineage data (Bertrand et al, 2010;Boisset et al, 2010;Lam et al, 2010;Yaniv et al, 2006;Ritsma et al, 2013;Rompolas et al, 2012), whereas methods based on single-cell deep sequencing now offer the potential to resolve individual phylogenies, even in human tissues (Shapiro et al, 2013;Treutlein et al, 2014). By combining these lineage-tracing approaches with static marker-based assays, snapshots of clonal evolution over time can be integrated with population-level measures to reveal how stem and progenitor cells contribute to tissue maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, progenitors expressing the same putative stem cell marker can exhibit heterogeneous fate choices (Graf and Stadtfeld, 2008), while stem cells with different expression profiles may behave similarly in the long term. Finally, recent studies in disparate tissues have also shown that cells normally committed to differentiation can, in the course of regeneration following the targeted ablation of endogenous stem cell populations, re-acquire the hallmark properties of tissue stem cells, including the potential for long-term self-renewal (Rompolas et al, 2012;van Es et al, 2012;Tata et al, 2013;Yanger et al, 2014;Tetteh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As cells in the HG proliferate to promote hair growth, bulge SCs divide to replenish the follicular SC pool (Zhang et al 2009). To regulate their activity, follicle cells receive signals from surrounding dermal cells, including those in the dermal papilla (DP), a mesenchymal compartment associated with the HF (Greco et al 2009;Rompolas et al 2012;Chi et al 2013); neurons (Brownell et al 2011); smooth muscle cells (Fujiwara et al 2011); Ó 2014 Goldstein et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%